Improving the Value of Care for Veterans: Impacts of VA Payment Reform for Community‐Based Dialysis - Wang, V. (Health Serv Res, 2020)
End‐stage kidney disease (ESKD) is common among Veterans. VA’s limited capacity to deliver dialysis treatment means that VA relies heavily on community providers, making chronic dialysis the single largest VA expenditure for outpatient community care. In the past, VA paid for non‐VA dialysis on a local, ad hoc basis, with some payments greatly exceeding Medicare’s reimbursement rates. In 2009‐2011, the VA began implementing payment policies to standardize the process of pricing non‐VA dialysis care, beginning with the use of the Medicare fee schedule and national dialysis contracts with non‐VA dialysis facilities. This study examined the effect of VA’s standardized pricing policies on VA costs, access to non‐VA dialysis care, and patient outcomes. We used an interrupted time series design and 2006‐2016 data from VA, Medicare, and the US Renal Data System to identify Veterans receiving VA‐financed dialysis in the community from non‐VA providers. Changes over time in prices for non‐VA dialysis treatments and associated ancillary services were ascertained from >7 million VA‐paid community dialysis claims. We performed multivariable regression analyses using differential trend/intercept shift models to examine the effects of VA national contract pricing on (a) VA treatment prices for non‐VA dialysis, (b) access to non‐VA dialysis care defined as the number of non‐VA dialysis providers, and non‐VA dialysis providers’ publicly reported quality hospitalization and mortality rates, patient distance to non‐VA dialysis care, and (c) Veterans’ one‐year mortality, controlling for patient and facility fixed effects. National cohort of 24,130 VA‐enrolled Veterans who received ≥1 community‐based chronic dialysis treatment financed by VA in 2006‐2016. Before implementation of national contracts, treatment prices for non‐VA dialysis care varied widely across VA facilities from as little as $61 to as much as $1,575 per treatment. After implementation of national contracts, there was significantly reduced variation in the cost of treatment across individuals ($73.40 to $663.37) and the average price per dialysis session dropped by 40% (P < .001). Over the same time period, the average number of non‐VA dialysis facilities providing VA‐paid dialysis care increased from 19 to 37 and there were no changes in community dialysis facility quality (P ≥ .44) or 1‐year mortality (12% vs. 11%, P = .98). VA’s policy to standardize national dialysis contracts resulted in a substantial increase in the value of VA‐financed community dialysis care by reducing spending with no adverse effect on Veterans’ access to care nor on mortality. Our findings suggest it is possible to simultaneously lower costs while improving VA partnerships with community providers. National price setting may be a feasible approach for VA to improve the value of other community care services. Department of Veterans Affairs.